Objectives and interests of the tacnean insurrections during the crisis of the spanish colonial regime 1780-1813 - Choque Alanoca, Efrain (2021)
This article aimed to analyze the purposes and economic and political interests of the rebel nuclei that led the liberation movements in southern Peru (the townships of Arica and Tarapacá) during the period of independence from the concrete observation of the narratives outlined on the occasion of the insurrections of José Gabriel Condorcanqui (Túpac Amaru II), Francisco Antonio de Zela, and Enrique Paillardelle in the region. For the effect, a state of the question was carried out carrying out a content analysis of studies coming from national and international sources, for which a criterial sample was used based on essays coming from the representatives of the liberal narratives and the critical history; so it is carried out in the frame of a descriptive-explanatory design. The pertinence lies in the fact that the elucidation of such constitutive features of each movement will allow differentiating their nature and their assumed objectives in order to reconstruct with greater objectivity the development of independence in the Peruvian south. Conclusions suggest that there is a liberal-republican narrative of this process proposed by Rómulo Cúneo-Vidal (1921) and another of a critical-national type under construction sustained by the new history with Oscar Panty, among others. The first one saw in the Tupac Amaru movement a conspiracy against the system, calling its leaders as fearsome "bloodthirsty"; or the "(...) attack of the rebels" to the people of Tacna; while the new history sustains that with the movement of Tupac Amaru II begins a juncture of radical rupture - as part of the indigenous national movement - with the prevailing colonial system; while that of Zela constitutes an autonomist-reformist rebellion and that of Paillardelle one of separatist sign, but these last two within the movement of Creole liberation linked to merchants and provincial landowners